COGNITIVE PROCESSES IN WRITING OF TENTH GRADE STUDENTS AT SMAS AMIR HAMZAH MEDAN - Sinaga, Doni Setiawan; Gultom, Johannes Jefria (Universitas Negeri Medan, 2023)
The objective of this study was to explain the reasons behind the way cognitive processes of tenth- grade students occur in writing descriptive text. This study was conducted by using descriptive qualitative design. The data were collected by using students' writing and interview. The subjects of this study were the students of tenth grade at SMAS Amir Hamzah Medan. The findings of this study showed the reasons for tenth-grade students’ cognitive processes in writing were the students' habits of how they usually think about organizing their writing by determining the title and the subjects’ skills of composing an outline descriptive text, the different abilities to think in constructing sentences into text structures of descriptive text, namely identification, and description, and the students had the awareness to rethink their results by reading and reflecting on the text they had written and they revised errors in their text to ensure the results of writing descriptive text.